ANALISIS SIKAP MAHASISWA TERHADAP PEMBELAJARAN BAHASA INGGRIS ONLINE - Masniati Murni Ritonga; Ramadani Ramadani (BADAN PENERBIT STIEPARI PRESS, 2021)
Attitude is the essential factor that affected foreign language learning because it delayed on the feeling of the learners. The recent phenomena happened was that the development of technology and the shifting of learning portrait into digital vibes, it forced students to be master in operatinng technology spontanously, without any preparation and training. They should communicate via digital which was settled in English in it, the must be more accustomed in the used of English vocabulary, it such as autodidact learning or life learning. This study aimed to investigate the students’ attitude towards English when they were studying by digital (e-learning). The study was design in simple quantitative by using closed questionnaire. It was administered to the respondents (all of business administration students especially International Business concentration grade II Academic year 2019-2020 with sample 52 people. The content of the questionnaire use 3 components of attitude such as cognition, afection and conation. Furthermore it was analysed based Miles, Huberman and Saldana stage. It was found that 78% respondents responded positively (good). In another words, the students have goiod attitude towards e-English learning.